PERBEDAAN GENDER DALAM DUNIA KERJA DAN PERANANNYA PADA GAYA KEPEMIMPINAN - Dita Oki Berliyanti (Universitas Trisakti, 2002)
From long time ago, difference of gender at work caused many problems, nowadays there are more working women and more of them became a leader in a company or in an organization. Therefore it is necessary to know the role of each gender and the leadership style of them at work, especialy for woman. The paper argues employee give lots of influence in their leadership style to the woman organization.